Contribution of Dietary Intakes of Antioxidants to Homocysteine-Induced Low Density Lipoprotein (LDL) Oxidation in Atherosclerotic Patients - Seo, Hongseog (Yonsei University College of Medicine, 2010)
PURPOSE: Elevated circulating oxidized low density lipoprotein (Ox-LDL) levels are associated with increased risk of atherosclerosis, which may be due to high plasma homocysteine (Hcy) and low intakes of antioxidants. We investigated the contribution of dietary intakes of antioxidants to Hcy-induced LDL oxidation in atherosclerotic patients (AP) and controls. MATERIALS AND METHODS: Male AP (n = 101) who were confirmed by coronary angiography and 91 controls were evaluated by blood biochemistry and dietary intakes. To determine whether homocysteine is an independent risk factor for atherosclerosis, subjects were divided into three groups; low- (≤ 6.9 uM/L), normal- (7 uM-12 uM/L) and high- (≥ 12.1 uM/L) Hcy. RESULTS: Plasm levels of homocysteine and LDL were higher, but plasma apo A-I in HDL and folate were lower in the AP group. The odds ratio (OR) for the risk of atherosclerosis was 3.002 [95% confidence interval (CI), 1.27-7.09] for patients in the highest tertile with homocysteine ≥ 12.1 uM/L. AP having high homocysteine levels had low intakes of vitamin A, β-carotene and vitamin C. By logistic regression analysis, age, body mass index (BMI), plasma LDL, plasma folate, and low intakes of vitamin A and β-carotene were found to be risk factors for atherosclerosis in patients with high-Hcy, but dietary B vitamins including folate were not. CONCLUSION: A high-Hcy level was a risk factor for atherosclerosis in patients with high Ox-LDL levels. High intakes of antioxidants appeared to be a protective factor for atherosclerosis, perhaps exerting a pro-oxidative effect on LDL when combined with high levels of Hcy and LDL. However, more evidence for the benefits of B vitamins as a homocysteine-lowering therapy is needed.